NEGARA BAYANGAN CENDERUNG KORUPSI, SISI GELAP OTONOMI DAERAH - Amalia Syauket; Dwiseno Wijanarko (Jurnal Manajemen Publik dan Kebijakan Publik (JMPKP), 2021)
Abstract: Good Governance is crucial for the attainment of development goals and delivering the promises of democracy. However, it cannot be understood apart from the political regime and the political dynamic within which it exists. establising good governance in a traditional democracy such as Indonesia has its additional challenges. specifically, it attempt to show that currently low quality of governance in provinces accross Indonesia might be linked to the existence of shadow state. The shadow state phenomenon is a characteristic of the administration of governance in the post-New Order democratic transition period. Banten Province, led by the Governor of the Ratu Atut Chosiyah, is a perfect example of a shadow state. This paper is the result of a long research on the shadow state phenomenon in Banten, which is not far from Jakarta. The research method uses a qualitative approach using various literature sources with the phenomenological type. To achieve data validation, a continuous triangulation process was carried out. The substance of the material in this paper will try to explain the opportunities and challenges in developing the concept of good governance in the socio-political reality shadowed by a shadow country that is prone to corruption.